Homosexualité : la formulation d’une perspective sociologique [1967] - William Simon; John H. Gagnon (Genre, Sexualité et Société)
Homosexuality, as well as other forms of social or sexual deviance, has tended to require special conceptual approaches, approaches that all too often treat non-deviant forms of behavior (e.g., heterosexuality, noncriminal behavior, nonsuicidal behavior, etc.) as unexplained residual categories. The failure to link deviant and non-deviant behaviors or roles has produced a literature that grossly exaggerates the deviant component in behavior and role management. Often the deviant is located in a social landscape that has been stripped of everything but his deviant commitment. The present paper considers the homosexual within the conceptual framework of general developmental processes; it approaches homosexuality as a heterogeneous category, indicating the diversity of homosexual and non-sexual roles the homosexual may play, the significance of transitions associated with life-cycle changes, and, reversing the typical approach, takes into consideration the way in which non-sexual roles and commitments influence sexual roles and commitments.